2012
DOI: 10.1002/jcu.21917
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the ductus venosus—A case with favorable outcome after early signs of cardiac failure

Abstract: Absence of the ductus venosus (ADV) is a rare vascular anomaly. Its prognosis depends on the pathway of the umbilical flow to the systemic venous circulation, and the presence or absence of associated structural or chromosomal anomalies, sometimes resulting in hydrops fetalis. In cases with isolated ADV in the absence of associated anomalies, survival rates are as high as 85%, depending on the shunt situation. Here, we report a patient with ADV and extrahepatic umbilical vein drainage with favorable outcome af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Similarly, Staboulidou et al 8 reported that an absent DV as an isolated finding in fetuses with normal nuchal translucency resulted in healthy live births. Likewise, Hofmann et al 1 recently reported a fetus with a favorable outcome of agenesis of the DV. That fetus had communication of the UV to the right atrium, with subsequent cardiomegaly, which resolved at the age of 4 months.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Similarly, Staboulidou et al 8 reported that an absent DV as an isolated finding in fetuses with normal nuchal translucency resulted in healthy live births. Likewise, Hofmann et al 1 recently reported a fetus with a favorable outcome of agenesis of the DV. That fetus had communication of the UV to the right atrium, with subsequent cardiomegaly, which resolved at the age of 4 months.…”
Section: Discussionmentioning
confidence: 88%
“…The variant with extrahepatic shunts includes drainage of the UV into the internal iliac vein, the IVC (as in our cases), the renal vein, or directly into the right atrium, bypassing the liver completely. This variant may result in reduced perfusion and oxygenation of the liver, cardiomegaly, congestive heart failure, and intrauterine fetal death 1 , 6 , 10 – 13 . We have presented cases with extrahepatic shunts of the UV to the IVC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations